Paternal and Maternal Urinary Phthalate Metabolite Concentrations and Birth Weight of Singletons Conceived by Subfertile Couples - Messerlian, Carmen (Environ Int, 2017)
BACKGROUND: Ortho-phthalates are known endocrine disruptors. Prenatal phthalate exposure has been inconsistently associated with fetal growth and infant birth weight; however, the effect of paternal and maternal preconception exposure remains understudied. OBJECTIVES: To investigate associations of paternal and maternal preconception and maternal prenatal urinary phthalate metabolite concentrations with birth weight. METHODS: The study comprised 364 singletons born to 364 mothers and 195 fathers (195 couples) from the EARTH Study, a prospective cohort of couples from Boston, MA. Births were categorized by mode of conception: in-vitro fertilization based (IVF) (n=208) or non-IVF based (n=156, intrauterine insemination or non-medically assisted/natural conception). We measured urinary concentrations of eleven phthalate metabolites in maternal (n=1,425) and paternal (n=489) preconception and maternal prenatal (n=781) samples. Birth weight was abstracted from delivery records. Covariate-adjusted associations between log(e)-phthalate metabolite concentrations and birth weight were evaluated separately by mode of conception using multivariable linear regression. RESULTS: Each log(e)-unit increase in paternal urinary concentration of the sum of di(2-ethylhexyl) phthalate (ΣDEHP) metabolites was associated with a 90 gram (95% CI: −165, −15) decrease in birth weight among IVF singletons, but not among non-IVF singletons (18 grams; 95% CI: −76, 113). Additional adjustment for maternal prenatal ΣDEHP concentrations modestly strengthened findings among IVF singletons. While few associations were found with maternal preconception phthalate metabolites, we observed an inverse relationship between several maternal prenatal urinary phthalate metabolite concentrations and birth weight among IVF singletons in covariate-adjusted models. However, with further adjustment for specific paternal phthalate metabolite concentrations, these associations were attenuated and no longer significant. CONCLUSIONS: Paternal preconception urinary concentration of ΣDEHP metabolites was associated with a decrease in birth weight among IVF-conceived singletons. These results, if replicated, highlight the importance of preconception health, especially among subfertile couples.